Penguatan Literasi Ekonomi Syariah Berbasis Digital pada Majelis Taklim di Kota Bandung: Strengthening Digital-Based Sharia Economic Literacy at the Majelis Taklim in Bandung City - Srisusilawati, Popon; Nurhasanah, Neneng; Hamdani, Fahmi Fatwa Rosyadi Satria; Maulida, Ira Siti Rohmah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This International Community Service (PKM) activity aims to improve the understanding and skills of Islamic economic literacy among members of the Majelis Taklim (Islamic study group) in Bandung City. The background of this activity is based on the community's low understanding of Islamic economic principles and the minimal use of digital technology to support sustainable Islamic financial practices. A total of 39 participants from the Islamic Economics Taklim Assembly of Bandung City participated in a series of activities that included counseling and mentoring. The material provided covered basic concepts of Islamic economics, an introduction to muamalah contracts, the use of Islamic digital applications, and Islamic personal financial management. Evaluation results showed a significant increase in participants' knowledge scores, with an average pre-test of 52.72 increasing to 67.83 in the post-test, representing a 15.11-point increase in understanding. This suggests that this activity is effective in fostering Islamic economic literacy within religious communities. As a recommendation, this program can serve as a sustainable educational model and be replicated in various regions, with its effectiveness strengthened through synergy between universities, Islamic financial authorities, and halal digital industry players.